PERAN MAJELIS ADAT ACEH DALAM MENYELESAIKAN SENGKETA WARIS TANAH DI KECAMATAN TEMPUK TEUNGOH KOTA LHOKSEUMAWE - UCHA HADI PUTRI (Hukum Islam, 2019)
AbstractThere are three inheritance law systems in Indonesia, namely the Islamic inheritance system, the customary inheritance law system and the civil inheritance system. Inheritance law of a group of people is strongly influenced by the kinship form of the community itself. The Acehnese adheres to the parental kinship system, which means the inheritance system in providing the position of boys and girls, who both have the opportunity to become heirs. The kinship system in the parental community is based on both parents. Based on Law Number 40 of 1999 concerning the Privileges of Aceh in Article 3 paragraph 2, affirms that Aceh is a Special Region in the fields of custom, religion and education. The government provides space for local communities to revive existing customs in society, one of which is in the settlement of inheritance disputes resolved by the Majelis Adat Aceh (MAA). The author is interested in conducting research on the role of MAA in resolving disputes of land inheritance in the subdistrict of teungoh sub-district in lhokseumawe city, writing theses using empirical juridical methods which in reality in the field are associated with the legal aspects or legislation in force. The role of the MAA in resolving inheritance disputes has not been fully implemented, from the administrative system and the application of decisions from the MAA which are detrimental to the parties.AbstrakSistem hukum waris yang berlaku di Indonesia ada tiga yaitu, sistem Hukum waris Islam, sistem hukum waris Adat dan sistem hukum waris Perdata. Hukum waris suatu golongan masyarakat sangat dipengaruhi oleh bentuk kekerabatan dari masyarakat itu sendiri. Masyarakat Aceh menganut sistem kekerabatan parental artinya sistem waris dalam memberikan kedudukan anak laki-laki dan anak perempuan yaitu sama-sama mempunyai peluang untuk menjadi ahli waris. Sistem kekerabatan pada masyarakat parental didasarkan pada kedua orang tua. Berdasarkan Undang-Undang Nomor 40 Tahun 1999 Tentang Keistimewaan Aceh  pada Pasal 3 ayat 2, menegaskan bahwa Aceh adalah Daerah Istimewa dalam bidang adat, agama, dan pendidikan. Pemerintah memberikan ruang bagi masyarakat lokal untuk bangkit kembali adat yang ada dalam masyarakat, salah satunya dalam penyelesaian sengketa waris yang diselesaikan oleh Majelis adat Aceh. Penulis tertarik untuk melakukan penelitian tentang peran MAA dalam menyelesaikan sengketa waris tanah di kecamatan tempuk teungoh kota lhokseumawe, penulisan tesis menggunakan metode yuridis empiris yang  pada kenyataan di lapangan dikaitkan dengan aspek hukum atau perundang-undangan yang berlaku. Peran MAA dalam menyelesaikan sengketa waris belum sepenuhnya berjalan dengan baik, dari sistem administrasi maupun penerapan keputusan dari MAA.